HUBUNGAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) TERHADAP EFEKTIVITAS KINERJA PERAWAT DI RUMAH SAKIT HUSADA JAKARTA - Br Saragih, Dameria (Jurnal Kesehatan Holistic, 2024)
Introduction: According to the results of the 2020 Population Census (SP2020) conducted in September 2020, Indonesia has a population of approximately 270 million people, making it the fourth most populous country in the world. With such a large population, the government needs to address various societal needs, including those in the fields of law, economy, education, and especially healthcare. Objective: This study aims to examine the relationship between the Hospital Management Information System (HMIS) and nurse performance at Husada Hospital Jakarta. Method: This research uses a quantitative approach with a descriptive survey design. Results: Chi-square test results show a significance value of 0.012, which is less than 0.05, indicating that the alternative hypothesis (Ha) is accepted. This suggests a relationship between HMIS and nurse effectiveness. The Odds Ratio (OR) of 8.000 indicates that nurses who do not use HMIS effectively are 8 times more likely to be ineffective compared to those who use HMIS effectively. Conclusion: Optimal implementation of HMIS should be a priority to achieve operational efficiency and improve service quality in hospitals.